REKRUTMEN CALON PEGAWAI NEGERI SIPIL (CPNS) DARI JALUR TENAGA HONORER DIKABUPATEN KAMPAR TAHUN 2012 - Noviyanti Nurhasanah; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The human resource in a region government is the most important component that can determine whether all procedurs in region government run well or not. It will run well, if it is supported by the best quality of human resovrse. If so all of the purposes will be reached efedifically and efisienlyAll of the human resourse who work in a region government called sipil servant. Based on the data from Kampar Regency. There are so many honorers who are waiting to be sipil servants. They are willing to be sipil servants as soon as possible, because they have worked for many years as honorers. Beside that, they also have had all of the conditions to e sipil servant.A ppointment of temporary employee benefits in the sipil servant in Kampar Refency 2012 is give an effect if social stat good governance. Sometimes called position is defined as a rank or profession as a temporary employee who originally as a temporary employee sekeratariat Kampar Regency.Civil servants were needed and as many as 135 permanent employees have been appointed as civil servants and rests on the applicable provisions that met the demands of professionalism of civil servants candidates as expected in implementation terms of appointment of civil service candidates from these temporary employees in technical positions not so relevant because there are not appointed as civil servants.Keywords:Recruitmen, Employee, Good Government